Innovating when producing health care, practices, and knowledge: how to avoid doing "ever the same" - Cecilio, Luiz Carlos de Oliveira (Saúde e Sociedade, 2012)
Five theoretical-practical issues are presented and put into discussion in the article: the chimera of primary health care (the promise that never comes true about a primary health network being resolutive, qualified, care-managing, and life- promoting in every dimension as well as a preferential "entryway" for the health care system); the "manufactured user" and the "manufacturing user" (the tension between the disciplined user, guided by standardized and foreseeable procedures - the "ideal user" -, and the "real user", who is autonomous, nomadic, makes choices and subverts the rationality intended by the administrators); the disjunction regarding manager's time, expert's time, user's time (the different and almost always incompatible ways of "living the time" of the several social actors as far as the access to health care services is concerned); the feeling of uneasiness expressed by the administrators in relation to the micro political space of health management (the troublesome externality of the administrators regarding the micro political space of health care); the multiple systems that regulate the access and consumption of health care services or the operation of the real Brazilian National Health Service (SUS) as a social production (the formal/governmental regulation understood only as one of the regulatory logics involving the access to health care services). The author sustains that these five theoretical-practical issues help form a portfolio of matters for the debate over innovative practices concerned with the present-time SUS.